Implementasi Pembelajaran Tarjamah Melalui Whatsappgroup Bagi Siswa Kelas VII MTs Muhammadiyah Cambajawaya Gowa Sulawesi Selatan - Munawir Munawir; Nur Fadilah Amin (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2021)
The purpose of this study is 1. To find out how the implementation of learning through Whats App Group (WAG) for students VII MTs Muhammadiyah Cambajawaya Gowa, South Sulawesi.  2. To find out the supporting and inhibiting factors for the Implementation of Learning Tarjamah through Whats App Group for Class VII students of MTs Muhammadiyah Cambajawaya Gowa, South Sulawesi.  3. To find out the efforts made in the implementation of Tarjamah learning through Whats App Group (WAG) for Class VII students of MTs Muhammadiyah Cambajawaya Gowa, South Sulawesi. The type of research used is qualitative research. The subject of this research is the seventh grade teacher of MTs Muhammadiyah Camabajawaya Gowa South Sulawesi. The data collection technique used is the observation technique.  interviews, documentation. The results showed that the 1. Application of tarjamah learning through Whats App Group was ineffective and less flexible because there were several obstacles. 2. There ara factors that influence namely signal interference, cellphone memory full of lack of interaction, difficulty in knowing seriousness in learning, lack of student learning motivation, lack of online learning support facilities, and  difficult to understand the material provided, 3. Efforts made to overcome the obstacles that occur from the use of Whats App Group as a medium in online learning it is suggested that teachers are able to make variations in learning, especially by using features in the Whats App Group.